Green crime and the role of environmental courts - Walters, Reece (Crime, law and social change, 2013)
Environmental issues continue to capture international headlines and remain the subject of intense intellectual, political and public debate. As a result, environmental law is widely recognised as the fastest growing area of international jurisprudence. This, combined with the rapid expansion of environmental agreements and policies, has created a burgeoning landscape of administrative, regulatory and judicial regimes. Emerging from these developments are increases in environmental offences, and more recently environmental crimes. The judicial processing of environmental or ‘green’ crimes is rapidly developing across many jurisdictions. Since 1979, Australia has played a lead role in criminal justice processing of environment offences through the New South Wales Land and Environment Court (NSW LEC). This article draws on case data, observations and interviews with court personnel, to examine the ways in which environmental justice is now administered through the existing court structures, and how it has changed since the Court’s inception.